1998
DOI: 10.1136/ard.57.10.588
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps weakness in knee osteoarthritis: the effect on pain and disability

Abstract: Objectives-(1) To determine the importance of quadriceps strength, structural change, and psychological status in terms of knee pain in the community. (2) To determine the relative importance of quadriceps function, structural change, and psychological status with respect to disability in subjects with knee pain. Methods-300 men and women with pain and 300 controls without pain (aged 40-79) were seen. Isometric quadriceps strength (MVC) was measured and muscle activation was assessed by twitch superimposition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
296
3
29

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(353 citation statements)
references
References 36 publications
(31 reference statements)
25
296
3
29
Order By: Relevance
“…A relationship between depressive symptoms and physical function has been described in longitudinal studies not limited to individuals with arthritis, as summarized by Ormel et al (46), and in cross-sectional studies of knee OA (31,34,47,48). The demonstration in the current study that the status of mental health predicts subsequent physical function is important, given how function assessment might be biased by depressive symptoms.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…A relationship between depressive symptoms and physical function has been described in longitudinal studies not limited to individuals with arthritis, as summarized by Ormel et al (46), and in cross-sectional studies of knee OA (31,34,47,48). The demonstration in the current study that the status of mental health predicts subsequent physical function is important, given how function assessment might be biased by depressive symptoms.…”
supporting
confidence: 52%
“…A downward spiral of pain, weakness, and reduced self-efficacy may lead to substantial reduction in activity. In support of this paradigm, subjects with knee OA and pain were weaker than those without pain (34), and in OASIS, there was evidence of an interaction between strength and pain (38) as well as strength and self-efficacy (7), in evaluating the effects on physical function.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…O'Reilly et al observed lower quadriceps strength in symptomatic versus asymptomatic legs, but did not match case and control knees for radiographic disease stage (38). Berger et al reported significant differences in knee extensor strength between WOMAC total score tertiles, but not across different K/L grade strata (K/L grades Ͻ2 versus 2 versus Ն2) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced lower limb muscle strength is particularly marked in people with symptomatic knee OA (10,11). More importantly, several cross-sectional studies have established that reduced knee extensor strength in people with knee OA is strongly associated with increased pain and poor physical function (10 -12).…”
Section: Introductionmentioning
confidence: 99%